Building Up Inclusive Procurement Ecosystems through Digital Transformation - Gunawan, Edy; Mutaqin, Muhammad Iqbal (Ikatan Ahli Pengadaan Indonesia (IAPI), 2024)
This paper delves into the design and implementation of digital transformation within the Procurement Unit of the Ministry of Finance of the Republic of Indonesia (UKPBJ Kemenkeu). The study underscores the pivotal role of digital transformation in enhancing efficiency, effectiveness, transparency, accountability, collaboration, and sustainability in the procurement processes of goods and services. The transformation is anchored on four main pillars: changes in work patterns and governance, simplification of business processes, development of empowered human resources, and the implementation of a data-driven approach. These pillars are actualized through five interrelated initiatives that have led to eleven synergistic innovations. The paper concludes that these innovations ensure the effectiveness and efficiency of the digital transformation of procurement, providing sustainable positive impacts for the organization and all stakeholders involved in the procurement of goods and services.